2006
DOI: 10.1128/aac.50.5.1689-1695.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Accumulation and Activity of Quinolones in Ciprofloxacin-Resistant J774 Macrophages

Abstract: Ciprofloxacin is the substrate for a multidrug resistance-related protein (MRP)-like multidrug transporter in J774 mouse macrophages, which also modestly affects levofloxacin but only marginally affects garenoxacin and moxifloxacin (J. Active efflux is a general means developed by cells for protection against invasion by amphiphilic, potentially harmful molecules (18). In this context, overexpression of multidrug efflux pumps is now recognized as a common and widespread mechanism of resistance to anticancer ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 16 publications
4
32
0
Order By: Relevance
“…The present data extend our previous observations underlining the role of the ATP-energized efflux transporters for modulation of the accumulation and activity of antibiotics in macrophages (33,34,46,47). Specifically, we show here that the activity of P-gp in THP-1 human macrophages decreases the relative potency of daptomycin towards phagocytized S. aureus by reducing its cellular concentration.…”
Section: Discussionsupporting
confidence: 78%
“…The present data extend our previous observations underlining the role of the ATP-energized efflux transporters for modulation of the accumulation and activity of antibiotics in macrophages (33,34,46,47). Specifically, we show here that the activity of P-gp in THP-1 human macrophages decreases the relative potency of daptomycin towards phagocytized S. aureus by reducing its cellular concentration.…”
Section: Discussionsupporting
confidence: 78%
“…This was achieved by longterm culture in the presence of progressively increasing drug concentrations, a procedure successfully used to select cells with efflux-mediated resistance to anticancer agents (11) (while fluoroquinolones act as antibiotics by impairing bacterial topoisomerases at low concentrations, they inhibit the eukaryotic topoisomerases II and kill mammalian cells at large concentrations). The phenotype of these cells has been described in a previous publication (24). They display a markedly reduced accumulation of ciprofloxacin, which could be brought almost to control levels by ATP depletion or addition of typical inhibitors of MRP efflux transporters, such as probenecid or MK571.…”
mentioning
confidence: 92%
“…They display a markedly reduced accumulation of ciprofloxacin, which could be brought almost to control levels by ATP depletion or addition of typical inhibitors of MRP efflux transporters, such as probenecid or MK571. Additional studies comparing other quinolones in both wild-type and ciprofloxacin-resistant cells showed that moxifloxacin was not affected by this efflux transporter in both cell types, while levofloxacin and garenoxacin showed an intermediate behavior (23,24). Beyond displaying a markedly reduced accumulation of ciprofloxacin, these ciprofloxacinresistant cells provide a protected environment against ciprofloxacin for Listeria monocytogenes (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our model, moxifloxacin diffused and accumulated quickly in cellular compartments, killing the intracytoplasmic forms of L. monocytogenes within the first 3 h (2, 22, 30). Despite the overexpression and/or increased activity of the MRP-like ciprofloxacin transporters, reported in ciprofloxacinresistant J744 macrophages, the intracellular accumulation of moxifloxacin would not be significantly altered, as moxifloxacin is only partially effluxed (21,22).…”
Section: Figmentioning
confidence: 99%